A Comparative Clinical Evaluation of Efficacy of Tramadol As An Adjuvant To Bupivacaine En Brachial Plexus Block For Upper Limb Surgery - Regmi, Nabin Kumar; Subba, Sangeeta; Sharma, Uttam Chandra (Journal of Nepalgunj Medical College, 2017)
Background: In peripheral nerve blocks, adjuvants are added to local anaesthetics to improve the quality of anaesthesia and analgesia. We designed this randomized single blinded prospective study to compare the analgesic efficacy of tramadol used as an adjuvant to bupivacaine for supraclavicular brachial plexus block in patients undergoing orthopaedic surgeries of upper limb. Aim of study: In this study, we aimed to compare onset, duration and quality of analgesia along with respiratory, hemodynamic changes with tramadol as adjuvant to bupivacaine in supraclavicular brachial plexus block in the patients undergoing upper limb surgery. Method: In this prospective randomized control trial, two groups of 30 patients each were investigated. 28 ml. of 0.5% bupivacaine (plain) with 2 ml. normal saline was administered in group - I and 28 ml. of 0.5% bupivacaine (plain) with 2ml. (100 mg.) tramadol was administered in group - II. The onset of sensory and motor block, duration of analgesia, respiratory/hemodynamic parameters and post-operatively quality of analgesia via visual analogue scale were assessed. Results: The duration and quality of analgesia was significantly increased by adding tramadol in bupivacaine than bupivacaine alone (p=<0.001 and <0.001) whereas there was no statistically significant difference in onset of motor (p=>0.35) and sensory block (p=>0.75) and also hemodynamic and respiratory parameters.(HR p=>0.1, MAP p=>0.5, and SPO p=>0.5). Conclusion: The study suggests that tramadol when added to bupivacaine 2 for supraclavicular brachial plexus block enhances the quality of anaesthesia and analgesia without affecting respiratory/hemodynamic parameters. JNGMC Vol. 13 No. 2 December 2015, Page: 13-16